Western and Indigenous Conceptualizations of Self, Depression, and its Healing - Dr. , Tony B. Benning (International Journal of Psychosocial Rehabilitation, 2013)
Taking a comparative, cross -cultural perspective, this paper examines indigenous and western conceptualizations of de- pression and its healing, in relation to Indigenous and Western concepts of self and selfhood. What emerges from the re- view of relevant literature from anthropology, cultural psychiatry as well as cultural psychology is that the concept of an extended self, which is seemingly common to many Indigenous cultures, is reflected in the presentation of depression and in the way in which its healing is conceptualized in these cultures. Similarly, Western conceptualizations of depression and its treatments reflect Western concepts of the self. The implications for Western mental health researchers and clinicians working with individuals, who identify with Indigenous world views, are discussed